Interplay of strain mechanisms in morphotropic piezoceramics. (1st August 2015) - Hinterstein, M.; Hoelzel, M.; Rouquette, J.; Haines, J.; Glaum, J.; Kungl, H.; Hoffman, M.
Abstract: A large number of transducers, ultrasonic motors or actuators are based on lead zirconate titanate (PZT) piezoceramics, with compositions near the morphotropic phase boundary (MPB) where the relevant material properties approach their maximum. Since the best piezoelectric properties, in particular the highest recoverable strains, are observed for these MPB compositions with phase coexistences, a separate analysis of each phase is mandatory. Here we present a sophisticated method to correlate the macroscopic strain observations to mechanisms on the atomic scale. The technique allows a quantification of all contributing strain mechanisms such as lattice strain, domain switching and phase transition for each phase. These results indicate that the major strain contribution is of structural instead of microstructural origin and the electric field induced phase transition occurs through polarisation rotation. Such a mechanism could be generalised in other MPB piezoceramics and will be useful to design and optimise the next generation of high performance piezoelectric materials.